Effect of Firm Characteristics on Financial Inclusions: Evidence from Women Owned Enterprises in Kenya - Nguli, Judith Ndinda; Odunga, Robert Mukoswa (European Scientific Journal, ESJ, 2019)
The aim of the paper was to establish firm characteristics on financial inclusions; evidence from women owned enterprises in Kenya. This study employed positivism approach while adopting an explanatory survey research. The target population of study comprised 8000 women owned SMEs in the North Rift Region Economic Bloc Counties. Cluster sampling was employed to group SMEs in seven Counties, while simple random was used to select a sample size of 723. Using multiple regression model the findings revealed a negative and significant effect of firm age on financial inclusion and firm size has a positive and significant effect on financial inclusion. These results are useful in informing policies around educating women SMEs. Government of Kenya has invested enormous resources into SMEs growth. Therefore, these results will be used to package the literacy education geared on factors that contribute highest to financial inclusion. From the findings of the study, older SMEs are encouraged to keep up to date of the trends in business.